2020
DOI: 10.1093/jas/skaa361
|View full text |Cite
|
Sign up to set email alerts
|

Runs of homozygosity and analysis of inbreeding depression

Abstract: Pedigree information was traditionally used to assess inbreeding. Availability of high-density marker panels provides an alternative to assess inbreeding, particularly in the presence of incomplete and error-prone pedigrees. Assessment of autozygosity across chromosomal segments using runs of homozygosity (ROH) has emerged as a valuable tool to estimate inbreeding due to its general flexibility and ability to quantify chromosomal contribution to genome-wide inbreeding. Unfortunately, identification of ROH segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Conversely, a gain of 1.33 kg in the same trait was associated with an increase of 1% in ancient inbreeding (ROH < 4 Mb). A recent research study conducted in beef cattle by Sumreddee et al [38] demonstrated that although the recessive load is expected to be larger in longer ROH segments, short ROH segments (<5 Mb) can still harbor some deleterious mutations with substantial joint effects on some traits.…”
Section: Inbreeding Coefficientsmentioning
confidence: 99%
“…Conversely, a gain of 1.33 kg in the same trait was associated with an increase of 1% in ancient inbreeding (ROH < 4 Mb). A recent research study conducted in beef cattle by Sumreddee et al [38] demonstrated that although the recessive load is expected to be larger in longer ROH segments, short ROH segments (<5 Mb) can still harbor some deleterious mutations with substantial joint effects on some traits.…”
Section: Inbreeding Coefficientsmentioning
confidence: 99%
“…Additionally, the efficiency of purging of deleterious alleles from short ROH segments depends on several factors. In fact, Sumreddee et al [ 53 ] showed using the same data set and minimum length threshold (1 Mb) that the efficiency of purging depended on selection pressure and rate of inbreeding within the population. Thus, short ROH segments may still harbor harmful alleles in spite of their distant origin.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, short ROH segments may still harbor harmful alleles in spite of their distant origin. Furthermore, the large number of short ROH segments, each potentially with small effect, could collectively have a non-negligible contribution to inbreeding depression [ 53 ]. All these factors combined, complicate the discrimination between ROH segment classes using the proposed approach (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of pedigree information for the individuals included in this research, inbreeding coefficient (F) was estimated from runs of homozygosity (Froh) [ 28 ]. This was deemed as the most appropriate method to estimate the levels of inbreeding of both Muskellunge populations included in the study.…”
Section: Methodsmentioning
confidence: 99%